2020
DOI: 10.5539/ies.v13n7p65
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Self-Regulation and Higher-Order Cognitive Skills as Predictors of Preschool Children’s Early Academic Skills

Abstract: In this study, the direct and indirect relationships of children’s self-regulation skills and their higher-order cognitive skills of cognitive flexibility and abstraction skills with their early academic competencies are examined. Within the scope of the study, the mediating role of self-regulation skills with early academic competencies is investigated. In the study, inhibitory control, behaviour regulation, effortful control and cognitive flexibility are focused on as the main components of executi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 108 publications
0
1
0
Order By: Relevance
“…The role of self-regulation in in uencing cognitive exibility among students can be elucidated as follows: students exhibiting a higher degree of self-regulation tend to demonstrate enhanced cognitive exibility. This correlation indicates that individuals pro cient in managing their thoughts, emotions, and behaviors, when confronted with academic or life challenges, are likely to exhibit adaptable thinking and exible problem-solving strategies [19].…”
Section: Discussionmentioning
confidence: 99%
“…The role of self-regulation in in uencing cognitive exibility among students can be elucidated as follows: students exhibiting a higher degree of self-regulation tend to demonstrate enhanced cognitive exibility. This correlation indicates that individuals pro cient in managing their thoughts, emotions, and behaviors, when confronted with academic or life challenges, are likely to exhibit adaptable thinking and exible problem-solving strategies [19].…”
Section: Discussionmentioning
confidence: 99%
“…Table 6 displays how various higher-order thinking skills were developed in various modalities in the same lessons. To enhance student cognitive engagement in HyFlex, several strategies were employed, such as incorporating personalized questions (L7.1) (Rajeshwari & Krishna Prasad, 2020), encouraging learners to check their own learning progress (L12.1), fostering self-regulation (L1.2) (Sezgin & Ulus, 2020), making justifications (L4.2) (Curtis, 2019), making interpretations (L7.3) (Asari, 2019), participating in problem solving scenarios (L8.2) (Yulianto et al, 2019), doing simulations (L12.2) (Anindhyta et al, 2021), and conducting peer evaluations (L13.1) (Heilporn & Lakhal, 2021). Markedly, this study showed that HyFlex learning environment does not cause any inconvenience in the promotion of student cognitive development as long as learners are provided with appropriate strategies and equivalent learning opportunities.…”
Section: Fostering Higher-order Thinking Skills In Hyflexmentioning
confidence: 99%